2013
DOI: 10.1161/circheartfailure.112.000075
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Care of Patients With Acute Heart Failure Syndromes and Cardiac Troponin Elevation

Abstract: A cute heart failure (HF) syndrome (AHFS) is a major reason for visits to the emergency department (ED). 1,2 Patients with AHFS represent a heterogeneous group defined by new or worsening symptoms of HF that require urgent care. 3 Although several potential underlying or precipitating factors are implicated, ischemic heart disease contributes importantly as a pathogenetic factor in AHFS. 4 It is estimated that 50% to 70% of patients with AHFS have concomitant coronary artery disease; however, optimal managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Our patients with intermediate or elevated TnT had significantly lower LVEF (and therefore a higher percentage of patients with reduced LVEF) than those with normal TnT, a finding also in line with previous studies [4,6,24,26]. Perna et al and Felker et al observed that these differences were not statistically significant [9,22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our patients with intermediate or elevated TnT had significantly lower LVEF (and therefore a higher percentage of patients with reduced LVEF) than those with normal TnT, a finding also in line with previous studies [4,6,24,26]. Perna et al and Felker et al observed that these differences were not statistically significant [9,22].…”
Section: Discussionsupporting
confidence: 92%
“…In the PROTECT study, levels of cardiac TnT N 0.03 ng/mL were confirmed to be an independent predictor of the composite endpoint of cardiovascular/renal rehospitalization or death at 60 days; TnT N 0.01 ng/mL was only predictor on univariate analysis [13]. Finally, Braga et al also reported that elevated troponin was associated with a higher risk of death and cardiovascular hospitalizations at 30, 180 and 365 days [24].…”
Section: Discussionmentioning
confidence: 88%
“…Cardiac biomarkers are generally used for the diagnosis or assessment of heart diseases [4], [5], [6], [7]. Recent studies demonstrated that cardiac biomarkers can predict an increased risk for death in subjects in the general population [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of cardiac troponin are often found in patients with HF, [43][44][45][46] many times without any history or other evidence of myocardial ischemia, and even in the absence of coronary artery disease. In patients with HF, the presence of elevated cardiac troponin is associated with increased mortality and worse outcomes.…”
Section: Diagnostic Studiesmentioning
confidence: 99%